Facial skin rejuvenation by autologous dermal microfat transfer in photoaged patients: Clinical evaluation and skin surface digital profilometry analysis. Issue 8 (August 2017) - Trivisonno, Angelo; Rossi, Alfredo; Monti, Massimo; Di Nunno, Donato; Desouches, Christophe; Cannistra, Claudio; Toietta, Gabriele
Summary: Cumulative long-term exposure to solar ultraviolet radiation promotes premature skin aging characterized by wrinkle formation and reduced skin elasticity. In this study, we assessed whether microfat transfer could improve dermal and subcutaneous tissue thickness loss associated with photoaging. Twenty-one patients affected by facial photoaging (photodamage grade II–IV; age range 35–62 years; 19 females, 2 males; all of Caucasian origin) were treated using minimally invasive autologous dermal white fat transfer harvested with a recently designed microcannula. The results were determined by clinical assessment and patient self-evaluation and quantified by the Antera 3D ® dermal digital device for noninvasive, objective, reliable, and accurate assessment of facial skin texture, color, and wrinkle characteristics. Compared with the pretreatment condition, the increment in soft tissue volume and improvement in skin quality and texture were assessed by a dermatologist after treatment. In addition, instrumental evaluation by digital skin profilometry of the treated areas revealed a 41% reduction in average wrinkle depth (7.29 ± 1.04 × 10 −2  mm pretreatment vs. 4.31 ± 1.16 × 10 −2  mm at 90 days posttreatment; p < 0.001), improved skin texture, more homogeneous and uniform skin color, and declined facial hemoglobin and melanin concentrations. The majority of patients (above 90%) reported improvements in self-perception. No significant complications were reported throughout the study. In conclusion, by using digital profilometry analysis as an objective and innovative tool to determine the outcome of treatment, we demonstrated that autologous microfat transfer is a safe and well-tolerated procedure with measurable beneficial effects on facial skin aging.